Nyctalus noctula subsp. mecklenburzevi Kuziakin 1934 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Nyctalus noctula subsp. mecklenburzevi Kuziakin 1934 Synonyms: Nyctalus noctula subsp. montanus Kishida 1934. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Chiroptera - Family Vespertilionidae, pp. 451-529 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 472, DOI: 10.5281/zenodo.7316519